The effects of light regime on carbon cycling, nutrient removal, biomass yield, and polyhydroxybutyrate (PHB) production by a constructed photosynthetic consortium - Wicker, Rebecca J.; Autio, Heidi; Daneshvar, Ehsan; Sarkar, Binoy; Bolan, Nanthi; Kumar, Vinod; Bhatnagar, Amit (Elsevier, 2022)
Microalgae can add value to biological wastewater treatment processes by capturing carbon and nutrients and producing valuable biomass. Harvesting small cells from liquid media is a challenge easily addressed with biofilm cultivation. Three experimental photobioreactors were constructed from inexpensive materials (e.g. plexiglass, silicone) for hybrid liquid/biofilm cultivation of a microalgal-bacterial consortia in aquaculture effluent. Three light regimes (full-spectrum, blue-white, and red) were implemented to test light spectra as a process control. High-intensity full-spectrum light caused photoinhibition and low biomass yield, but produced the most polyhydroxybutyrate (PHB) (0.14 mg g−1); a renewable bioplastic polymer. Medium-intensity blue-white light was less effective for carbon capture, but removed up to 82 % of phosphorus. Low-intensity red light was the only net carbon-negative regime, but increased phosphorus (+4.98 mg/L) in the culture medium. Light spectra and intensity have potential as easily-implemented process controls for targeted wastewater treatment, biomass production, and PHB synthesis using photosynthetic consortia.
Keywords: Photosynthetic consortia; Biological wastewater treatment; Nutrient removal; Photobioreactor; Polyhydroxybutyrate (PHB)